The Parents’ Ratings of the Quality of TV Teaching during the Pandemic Caused by the COVID-19 virus - Šimonji Černak, Ruženka J.; Marić, Mia R.; Beljanski, Mila B. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Because of the COVID-19 pandemic, the conditions in the state of emergency had forced the bigger part of school lessons in primary schools and highschools to be broadcasted on the public media services RTS 2 and RTS 3, as well as on the platform RTS Planeta. In that sense, parents had a big role and responsibility in educating their children. In this paper, we present the results of a study concerning primary school parents’ (mostly mothers) perception on TV teaching, which is a part of a broader research on distance learning. The research was conducted on the sample of 554 parents from Serbia. A newly constructed online questionnaire for the purpose of this research was used. The quality of TV teaching was assessed through nine items. The results showed that parents equally percieve the advantages and disadvantages of TV learning. Parents estimate that there is a clear teaching schedule and that the content is shown in an appropriate pace. The parents’ perceptions differ according to the place of living, degree of education, employment status during the state of emergency, as well as the number of school-age children in the family. The research findings provided guidelines for further improvement in teaching practices in emergency conditions and gave a preliminary image of the parents’ perception on TV teaching.